1999
DOI: 10.1021/jp984236p
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Pump−Probe Spectroscopy of the B850 Antenna Complex of Rhodobacter sphaeroides at Room Temperature

Abstract: The photosynthetic bacterium Rhodobacter sphaeroides contains a light-harvesting antenna complex (LH2) with a ring of interacting bacteriochlorophyll molecules (B850). Excitation of membrane-bound LH2 complexes with low-intensity, femtosecond pulses causes changes in absorption and stimulated emission that initially depend on the excitation wavelength but relax to a quasiequilibrium with a time constant of 100 ± 20 fs. Excitation on the blue side of the B850 absorption band is followed by a shift of the signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
150
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(158 citation statements)
references
References 36 publications
7
150
1
Order By: Relevance
“…Recently, high-resolution crystal structures of some peripheral light-harvesting complexes of photosynthetic purple bacteria (1-3) have become available, enabling us to study the basic principles of the highly efficient collection of solar energy (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Recently, high-resolution crystal structures of some peripheral light-harvesting complexes of photosynthetic purple bacteria (1-3) have become available, enabling us to study the basic principles of the highly efficient collection of solar energy (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…0.1 (De Caro et al, 1994 ;Joo et al, 1996 ;Malkin, 1996 ;Kennis et al, 1997 ;Nagarajan et al, 1999). The rate constant of this decay is less than 100 fs (Joo et al, 1996 ;Nagarajan et al, 1999). If we take the view that the B850* excited state is delocalized over a few of the B850 Bchla molecules, this rapid loss of polarization probably represents ultrafast migration of this excited state around the B850 ' ring '.…”
Section: The Structure Of Antenna Complexesmentioning
confidence: 99%
“…Similarly, as with the B800 excited state population, the energy transfer between the B850 Bchla molecules can be explored by recording the decay of the anisotropy of their excited state population (Jimenez et al, 1996 ;Pullerits & Sundstro$ m, 1996 ;Chachisvilis et al, 1997 ;Ma et al, 1997 ;Nagarajan et al, 1999 ;Sundstro$ m et al, 1999). However, the interpretation of this is complex.…”
Section: The Structure Of Antenna Complexesmentioning
confidence: 99%
“…The high initial anisotropy was ascribed to a coherent excitation of a degenerate pair of states with allowed optical transitions and then relaxation to states at lower energies which have forbidden transitions. Nagarjan et al [6] concluded, that the main features of the spectral relaxation and the decay of anisotropy are reproduced well by a model considering decay processes of electronic coherences within the manifold of the excitonic states and thermal equilibration among the excitonic states. In that contribution the exciton dynamics was not calculated explicitly.…”
Section: Introductionmentioning
confidence: 96%
“…Time-dependent experiments [3,4] led for the B850 ring in LH2 complex to conclusion that the elementary dynamics occurs on a time scale of about 100 fs [5,6,7]. For example, depolarization of fluorescence was studied already quite some time ago for a model of electronically coupled molecules [8,9].…”
Section: Introductionmentioning
confidence: 99%